2020
DOI: 10.1016/j.virol.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The use of cells from ANPEP knockout pigs to evaluate the role of aminopeptidase N (APN) as a receptor for porcine deltacoronavirus (PDCoV)

Abstract: A B S T R A C TThe coronaviruses, porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and porcine deltacoronavirus (PDCoV) represent important sources of neonatal diarrhea on pig farms. The requirement for aminopeptidase N (APN) as a receptor for TGEV, but not for PEDV, is well established. In this study, the biological relevance of APN as a receptor for PDCoV was tested by using CRISPR/Cas9 to knockout the APN gene, ANPEP, in pigs. Porcine alveolar macrophages (PAMs) from ANPEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Our results on the delayed PDCoV-specific neutralizing antibodies production, and a reduced extent of gross and histopathological lesions on small intestine in DKO pigs compared to WT pigs are consistent with this previous suggestion that pAPN may play a role but is not the only path for PDCoV cell entry. Interestingly, a recent study showed that PAMs, but not lung fibroblast-like cells, from pAPN knockout pigs showed resistance to PDCoV infection ( Stoian et al, 2020 ), a finding consistent with our in vitro experiments showing that DKO PAMs exhibit decreased susceptibility to PDCoV infection. In addition, pAPN knockout pigs are susceptible to PDCoV when virus levels were detected using qRT-PCR, and virus neutralization activity was measured, although the extent of tissue lesions between the KO and WT groups was not compared ( Stoian et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results on the delayed PDCoV-specific neutralizing antibodies production, and a reduced extent of gross and histopathological lesions on small intestine in DKO pigs compared to WT pigs are consistent with this previous suggestion that pAPN may play a role but is not the only path for PDCoV cell entry. Interestingly, a recent study showed that PAMs, but not lung fibroblast-like cells, from pAPN knockout pigs showed resistance to PDCoV infection ( Stoian et al, 2020 ), a finding consistent with our in vitro experiments showing that DKO PAMs exhibit decreased susceptibility to PDCoV infection. In addition, pAPN knockout pigs are susceptible to PDCoV when virus levels were detected using qRT-PCR, and virus neutralization activity was measured, although the extent of tissue lesions between the KO and WT groups was not compared ( Stoian et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, a recent study showed that PAMs, but not lung fibroblast-like cells, from pAPN knockout pigs showed resistance to PDCoV infection ( Stoian et al, 2020 ), a finding consistent with our in vitro experiments showing that DKO PAMs exhibit decreased susceptibility to PDCoV infection. In addition, pAPN knockout pigs are susceptible to PDCoV when virus levels were detected using qRT-PCR, and virus neutralization activity was measured, although the extent of tissue lesions between the KO and WT groups was not compared ( Stoian et al, 2020 ). Our findings are in line with this study reporting that pAPN knockout pigs are still susceptible to PDCoV.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations